Innovative Solutions in Orbital Fracture Management: The Role of Computer-aided Design and Computer-aided Manufacturing Technology - Abhishek Kumar Gupta; Rekha Gupta; Aishwarya Saini; Vashi Narula; Rohit Kumar Singh (Contemporary Clinical Dentistry)
Being the intricate architecture of the maxillofacial region, rehabilitation of maxillofacial abnormalities is relatively hard for most maxillofacial surgeons. Orbital roof fractures are among the most uncommon craniofacial abnormalities. The fact that these fractures “grow” makes treatment challenging. An encephalocele can form as a result of a hemorrhage or swelling caused by a dural rupture. These “growing” fractures are prevalent in children. The etiology of these fractures is uncertain; however, a dural laceration usually occurs along the fracture line. After a latency period, clinical signs and symptoms of an expanding fracture of the orbital roof are observed. During this latent time, the fracture expands in size during the growth stage, causing the brain to herniate and cause ocular symptoms such as eyelid swelling or exophthalmos. Computed tomography scans are commonly used to diagnose this type of fracture, and computer-aided design and computer-aided manufacturing (CAD/CAM) can be used to render the three-dimensional model for treatment planning. Growing orbital roof fractures must be investigated as a differential diagnosis in patients with chronic ocular complaints. The case study that follows sheds light on the relevance of the use of CAD/CAM technology for such patients in treatment planning.